Time truncated group chain sampling strategy for pareto distribution of the 2nd kind - Razzaque Mughal, Abdur; Zain, Zakiyah; Aziz, Nazrina (MAXWELL Science Publication, 2015)
The main goal of this study is to propose a chain Group Acceptance Sampling Plan (GASP) when the life time of a product follows the Pareto distribution of the 2nd kind. The design parameters such as the minimum group size and operating characteristic values are obtained by satisfying the producer’s and consumer’s risks at the specified quality level, acceptance number and the test termination time.A classical example is considered in order to compare the proposed plan with some existing plans.